(untitled) (Eurasian Journal of Ecology, 2016)
Codonopsis is very valuable medicinal raw materials in national medicine. Preparations codonopsis promote normalisation practically all important functions of an organism. Since contain the biogene stimulators possessing ability to strengthen protective forces of an organism and to stimulate reparation processes in fabrics.